O Forte São Joaquim e a construção da fronteira no extremo norte: a ocupação portuguesa do vale do rio Branco (1775 - 1800) - Gomes Filho, Gregorio Ferreira (2012)
This study is related to the research line Integração, Política e Fronteira of the Post graduation Program in History of the Federal University of Santa Maria and aims to analyze the occupation of the Rio Branco valley by the Portuguese from 1775 to 1800, after the construction of the São Joaquim Fortress. It investigates to what extent the construction of the São Joaquim Fortress in the Rio Branco valley from 1775 and on favored the occupation of the region by the Portuguese and the construction of the far north frontier in the period 1775 1800. In order to develop the research, travelers and chronicles writers‟ reports were used as primary sources, in special colonial employees‟ reports. These were compared with documents about Grão-Pará and Rio Negro available at the Arquivo Histórico Ultramarino (AHU), iconography, cartography, among other primary sources. Alongside the study, it was observed that the construction of the fortress in the region of Rio Branco valley started, through its members, a new relation between Indians and non-Indians in that territory, brought the Portuguese State closer to the region which was object of dispute with other European conquerors and also led to Portuguese strategies to consolidate the occupation of the region. It was also observed the important role of these members of the military base as well as the diverse indigenous groups of the Rio Branco for the construction of the northern frontier. The indigenous people became very important historical subjects and were disputed by the settlers because the Indians‟ loyalty was essential to define the possession of the territory. In this scenario, it is possible to perceive not only a context of power relations between dominant people and dominated ones, but also space for negotiation, once the indigenous people tried to please their own needs.